Factors Affecting Demands for Development Housing Area in Regency West Lombok - Putri, Riska Ananda; Sutanto, Himawan; Suriadi, Irwan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of price, income, distance, facilities, and family size in a way that is both damn and simultaneous to request development housing in West Lombok Regency, Labuapi District. The type of research used in this research is an associative quantitative method. Testing was carried out on 43 respondents spread across four housing complexes, namely Grand Muslim Housing, Lingkar Muslim Housing, Lingkar Asri Housing, and Griya Taman Sari Housing. Data was obtained by distributing questionnaires and taking research samples using the purposive sampling method. Results analysis show that, in a way, from the five variables used in this research, there are three variables that have a positive effect and are significant, namely prices with a significant value of 0.001 < 0.05, income with a significant value of 0.000 < 0.05, and facilities with a facility value of 0.038 < 0.05. Meanwhile, the distance variable with a significant value of 0.532 > 0.05 and the number of families with a significant value of 0.668 > 0.05 have an insignificant effect on the demand for housing construction in West Lombok Regency, Labuapi District.